Cementation of Full Coverage Metal Crowns in Dogs. (March 2018) - Wingo, Kipp
This step-by-step article describes the technique for cementation of a full metal prosthodontic crown on the maxillary fourth premolar tooth of a dog using a common resin-based cement.